2019
DOI: 10.3390/genes10030202
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Characterization of Three Glucosinolate Transporter (GTR) Genes from Chinese Kale

Abstract: Chinese kale is a native vegetable in Southern China and the flowering stalk is the most commonly used edible part due to its high glucosinolate content and other nutritional qualities. The GTR protein played important roles in the glucosinolate transport process. In this study, three BocGTR1 genes were cloned from Chinese kale for the first time. Their gene structure, physicochemical properties, signal peptides, transmembrane structures, functional domains, second and third-order protein structures, and phylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…The total glucosinolate content was significantly decreased in mature leaves. 22 The concentration of sulforaphane in broccoli sprouts (1,153 mg/100 g DW) is about 10 times greater than mature broccoli (44-171 mg/100 g DW). 23 It was well-known that abiotic stress, such as supplementation of Se to plants, can lead to increased production of phenolic compounds.…”
Section: Discussionmentioning
confidence: 96%
“…The total glucosinolate content was significantly decreased in mature leaves. 22 The concentration of sulforaphane in broccoli sprouts (1,153 mg/100 g DW) is about 10 times greater than mature broccoli (44-171 mg/100 g DW). 23 It was well-known that abiotic stress, such as supplementation of Se to plants, can lead to increased production of phenolic compounds.…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, the application of JA and SA to Arabidopsis and Brassica has been shown to increase the accumulation of GLSs [30][31][32] . Furthermore, recent studies showed that SA treatment stimulated the gene expression of GTR1 in Chinese kale 33 . These studies showed the possibility of interactions between SA and AtGTR1.…”
Section: Discussionmentioning
confidence: 99%
“…In B. oleracea var. chinensis Lei, two GSL transporters BocGTR1a and BocGTR1c were identified, which express predominantly in the leaves and buds ( Jiang et al, 2019 ) with a variable expression pattern that also depends on the plant developmental stages and various abiotic and biotic stress conditions. In addition to similar transmembrane topology, three-dimensional structure, and functional domains, these two transporters also showed more than 81% amino acid sequence homology with A. thaliana GTR proteins, which indicates their related functionalities.…”
Section: Plant Secondary Metabolite Transporters: Functional Relevance and Approaches For Their Discovery And Characterizationmentioning
confidence: 99%